Implementasi Strategi Pemasaran Digital dalam Meningkatkan Brand Awareness melalui Optimasi Media Sosial Instagram & TikTok di Tanzif - Rico Hadeta Saputra; Diana Nur Azizah; Eman Sulaeman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze and implement an effective digital marketing strategy in increasing brand awareness of Tanzif, a natural soap brand, through optimizing the use of Instagram and TikTok social media. With an approach that involves content marketing and paid ads. The project focused on increasing brand awareness through the engagement rate of the Tanzif brand. The results obtained from the project implementation showed an increase in engagement rate on the Instagram platform and a decrease on the TikTok platform over the 3 months of the project, with Instagram from 0.96% to 1.35% and TikTok 7.48% to 5.77%. The decrease on the TikTok platform was due to audience growth that was not matched by an increase in engagement. In addition, there was an increase of 40 Instagram followers and 219 followers on TikTok. These findings suggest that the content-based marketing and paid advertising strategies implemented were successful in attracting audience attention. The recommendations resulting from this research are to continue the use of content calendar and content pillar to ensure content consistency, as well as maximizing Instagram features such as Reels, TikTok videos, and live streaming to expand market reach, collaboration with micro-influencers and improved visual product documentation are highly recommended. Regularly analyzing account performance on social media is also necessary to ensure the effectiveness of the marketing strategies implemented.